The effects of structured input and traditional instruction on the acquisition of the English causative passive forms: An eye-tracking study measuring accuracy in responses and processing patterns. (November 2022) - Benati, Alessandro
The present study explores the effects of structured input and traditional instruction on the acquisition of English causative passive forms using online measurements (eye-tracking). Previous empirical research investigating the effects of processing instruction through offline measurements (sentence and discourse) has overall shown positive results for this pedagogical intervention. Research investigating the main factor responsible for the effectiveness of processing instruction has confirmed that it is the structured input component that is the causative factor for the positive effects of processing instruction. The main questions of this study are: (1) what are the effects of structured input and traditional instruction on accuracy when measured by an eye-tracking picture selection task? (2) would possible difference in accuracy between structured input and traditional instruction be accompanied by changes in eye-movement patterns? To provide answers to the two questions formulated in this study, one eye-tracking study was carried out. Fifty-two adult learners (aged 19–21 years) participated and were assigned to one of two groups: structured input ( n = 26) or traditional instruction ( n = 26). Neither instructional groups received explicit information. A pre and post-training design was adopted and the two groups received two different instructional treatments (structured input vs. traditional instruction). Participants were assessed through a picture selection eye-tracking task to measure accuracy and eye-movement patterns while they were processing auditory sentences. Results of the eye-tracking task indicated that the structured input group achieved significantly higher accuracy scores compared to the group receiving traditional instruction. The main findings from the present study reveal that structured input training causes a change in learners' eye-movement patterns.